Race and Masculinity in Gay Men’s Pornography: Deconstructing the Big Black Beast - Brian Curtin (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2023)
Review of the book Race and Masculinity in Gay Men’s Pornography: Deconstructing the Big Black Beast, by Desmond Francis Goss.